Certifiable software applications. 2, Support processes - Boulanger, Jean-Louis (London : ISTE Press, 2016)
Certifiable Software Applications 2: Support Processes explains the process to achieve a certifiable application. This concerns several major topics, skill management, data preparation, requirement management, software verification, and software validation. In addition, analysis of the impact of the use of COTS and pre-existing software on certifiable software is presented. Finally, the last support process concerns the management of commercial tools, the creation of a specific tools, and therefore the qualification of tools, which is based on their impact on the final software.
Online resource, title from PDF title page (EBSCO, viewed January 25, 2017).
Includes bibliographical references and index.
Keywords: Application software -- Development; COMPUTERS -- Software Development & Engineering -- General; Application software -- Development; Electronic books; Electronic book